Response of peripheral blood mononuclear cells to conditioned medium from cultured oral squamous cell carcinomas - Cristiane Miranda França; Fabiana Mesquita Barros; Monica Andrade Lotufo; Kristianne Porta Santos Fernandes; Ricardo Carneiro Borra (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The current study investigated the capacity for tumor factors secreted by head and neck squamous cell carcinoma (HNSCC) cell lines, KB, KB16, and HEP, to induce the secretion of various cytokines from peripheral blood mononuclear cells (PBMCs). PBMCs were isolated from blood samples collected from six healthy volunteers and these cells were incubated for 6, 24, 48, or 72 hours in the presence of 50% conditioned medium collected from cultured cell lines pretreated with, or without, stimulants such as phytohemagglutinin (PHA) or lipopolysaccharides (LPS). Aliquots of each supernatant were then assayed for levels of IFN-Γ, vascular endothelial growth factor (VEGF), TNF-α, and IL-4 using enzyme linked immunosorbent assays (ELISAs). Data collected were analyzed using Student's t-test, an ANOVA test followed by Tukey's test, and tests of Pearson's Correlation. PBMCs cultured with KB16-conditioned medium produced the highest levels of IFN-Γ. VEGF was also detected in conditioned media collected from all of the squamous cell carcinoma (SCC) cell lines used, and a significant difference in VEGF levels between control and KB- or KB16-conditioned media was observed. TNF-α was secreted by all PBMC groups within 6 hours of receiving conditioned media, and these levels increased up to the 24 hour timepoint, after which levels of TNF-α stabilized. In contrast, none of the supernatant samples contained detectable levels of IL-4. In combination, these data suggest that direct contact between fresh human PBMCs and conditioned media from tumor cells induces the secretion of TNF-α and VEGF by PBMCs, and this represents an initial angiogenic response.